Kavyaśāstra aura kāvya : Bhāratīya sāhitya aura sāhityaśāstra ke antaḥsaṅgharsha aura antaḥsam-bandha kā vivecana - Tripathi, Radhavallabh, 1949- (Maikamilana, 1982)
Study of Sanskrit poetics and poetry.